Determination of α-mannan content in composite yeast cultures by enzymatic hydrolysis HPLC-UV method - Zhang, Xiaojie; Yang, Lan; Lian, Haifei; Xu, Zixuan; Yun, Zichen; Xu, Xiaohui; Liu, Shixiong; Luo, Qifei; Zolzaya, Majigsuren; Liu, Dacheng (Frontiers in Nutrition, 2025)
BackgroundComposite yeast culture (CYC) serves as an important functional feed additive. The content of its active ingredient, α-mannan, directly affects product quality and efficacy. However, due to the complex matrix of CYC, establishing a highly specific and accurate quantitative method for α-mannan remains a challenge.MethodsThis study aimes to establish an analytical method based on enzymatic hydrolysis combined with high-performance liquid chromatography equipped with an ultraviolet detector (HPLC-UV) for the quantification of α-mannan in CYC. The method involved the specific enzymatic hydrolysis of α-mannan in the sample using α-mannosidase, followed by the release of mannose, which was then derivatized with 1-phenyl-3-methyl-5-pyrazolone (PMP) and analyzed by HPLC-UV. The actual content of α-mannan was calculated using a formula.ResultsMethod validation results showed that mannose exhibited good linearity within the concentration range of 0.5–400 μg/mL, with a correlation coefficient of 0.99998. The limit of detection (LOD) and limit of quantification (LOQ) were 0.063 mg/L and 0.208 mg/L, respectively. The average recovery rate was 88.020%−94.204%, with a relative standard deviation (RSD) ranging from 0.702% to 2.259%, indicating that the method has high accuracy and good precision.ConclusionThis study successfully established an efficient and reliable HPLC-UV detection method suitable for the specific quantitative analysis of α-mannan in CYC. The method exhibited good reproducibility and operational feasibility, providing robust technical support for quality control of CYC products and related functional component research.